Analisis Bentuk Perlindungan Hukum Terhadap Penggunaan Merek pada Kelas Barang dan Jasa yang Sama - Hans, Callista; S.T. Kansil, Christine (Universitas Ekasakti, 2023)
This research explore the aspect of legal protection of brand rights users by other registered brands ini Indonesia based on the Law Number (No.) 20 of 2016 on Trademark and Geographical Indicatios. Brand holds important role in the world of trade and economics, create a crucial legal protection of infringement prevent that could harm brand owners. This research review the mechanism of legal protection that applied for registered brands and conflict resolution procedure related to brand right users by other registered brands in the same classification. This research describe that Indonesia has a suffice legal framework in legal protection with Law Number (No.) 20 of 2016 on Trademark and Geographical Indicatios as the main law. Registered brand owner gets 10 years legal protection that can be extended, give them legal certainty while running their business. For further, various types of sanctions, not only criminal, civil, but also administrative, available to handle trademark infringements. Nonetheless, this research aslo indentify challenges, especially in knowledge and awareness of trademark protection. Both law subjects and government need to perform more effective socialization and actively solve this problem to increase the awareness of trademark registration. To be concluded, comprehensive knowledge of trademark protection and the awareness of trademark registration is the main element to support business growth and trademark protection in Indonesia. In this context, the effective law enforcement becomes important to prevent trademark infringements and maintain public justice.